2019
DOI: 10.1038/s41388-019-0795-5
|View full text |Cite|
|
Sign up to set email alerts
|

Upregulated claudin-1 expression promotes colitis-associated cancer by promoting β-catenin phosphorylation and activation in Notch/p-AKT-dependent manner

Abstract: In IBD patients, integration between a hyper-activated immune system and epithelial cell plasticity underlies colon cancer development. However, molecular regulation of such a circuity remains undefined. Claudin-1(Cld-1), a tight-junction integral protein deregulation alters colonic epithelial cell (CEC) differentiation, and promotes colitis severity while impairing colitis-associated injury/repair. Tumorigenesis is a product of an unregulated wound healing process and therefore we postulated that upregulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 37 publications
(62 reference statements)
0
21
0
Order By: Relevance
“…The upregulated claudin-1 expression can inhibit the goblet cell differentiation and promote colitis-associated cancer in a Notch-dependent manner [ 38 ]. The decreased claudin-1 expression by BLIDF supplementation suggests that BLIDF can alleviate colitis severity in DSS-treated mice [ 39 , 40 ]. The anti-colitis effects of BLIDF were abolished when the gut microbiota was depleted by antibiotics, suggesting that the anti-colitis effects of BLIDF are highly dependent on intestinal microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…The upregulated claudin-1 expression can inhibit the goblet cell differentiation and promote colitis-associated cancer in a Notch-dependent manner [ 38 ]. The decreased claudin-1 expression by BLIDF supplementation suggests that BLIDF can alleviate colitis severity in DSS-treated mice [ 39 , 40 ]. The anti-colitis effects of BLIDF were abolished when the gut microbiota was depleted by antibiotics, suggesting that the anti-colitis effects of BLIDF are highly dependent on intestinal microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, the present analysis not only added an additional three studies [ 43 , 44 , 48 ] but also examined the HR for OS and DFS of CRC. We also included all claudin-1 detection methods, including ELISA and RT-PCR, which were excluded in the analysis by Jiang et al In addition, new studies have emerged reporting on claudin-1 and CRC since the previous similar meta-analysis was published in 2017 [ 48 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“… 42 In the development of colitis and CAC, macrophages infiltrate the colon and release a series of cytokines to remodel the affected microenvironment and promote the initiation and progression of colon cancer. 43–45 The inhibition of macrophage infiltration or activation induces an efficient antitumor and anti-colitis effect, respectively, in mice and also in clinical use for humans. 43 , 46 , 47 Our study demonstrated that the number of activated macrophages that infiltrated the colons of GDC-0575-treated CAC and colitis mice decreased compared with that of the DMSO-treated control mice; this decrease was accompanied by a reduction in the expression of pro-inflammatory cytokines that were released by the infiltrating macrophages.…”
Section: Discussionmentioning
confidence: 99%